A flexible lab-on-a-chip for the synthesis and magnetic separation of magnetite decorated with gold nanoparticles1. Issue 8 (21st April 2015) - Cabrera, Flávio C.; Melo, Antonio F. A. A.; de Souza, João C. P.; Job, Aldo E.; Crespilho, Frank N.
<x xml:space="preserve">Abstract</x> The preparation of controlled amounts of magnetite nanoparticles decorated with gold nanoparticles without organic solvents, surfactants, or heat treatment is presented. For this, natural-rubber-based microfluidic device (NRMD) was used as a flexible lab-on-a-chip.